Validity and Reliability Evidence of the SportRec Track and Field Talent Test Battery for Individuals with Intellectual Disabilities - Nagoor Meera Abdullah; Wahidah Tumijan; Zarizi Ab Rahman; Novri Gazali; Sri Sumartiningsih (Universitas Negeri Semarang, 2025)
Abstract. The present study evaluated the construct validity and reliability of the Track and Field SportRec Talent Test Battery (SRTTB) designed for individuals with intellectual disabilities. Talent identification plays an important role in optimizing athletic potential and supporting inclusive sports development. A total of 74 male students with intellectual disabilities aged 14–20 years from a special school in Klang participated in the study. Participants completed several physical performance tests, including the standing long jump, 30 m sprint, push-up, seated medicine ball throw, standing overhead medicine ball throw, standing backward overhead medicine ball throw, and 20 m intermittent fitness test. Data analysis was conducted using IBM SPSS version 30 to examine construct validity and test–retest reliability. Construct validity was assessed through convergent and discriminant validity analyses, while reliability was evaluated using the Intraclass Correlation Coefficient (ICC). The findings demonstrated excellent reliability for the standing long jump (ICC = 0.94), 30 m sprint (ICC = 0.89), push-up (ICC = 0.97), standing overhead medicine ball throw (ICC = 0.84), standing backward overhead medicine ball throw (ICC = 0.91), and VO₂max test (ICC = 0.99). The seated medicine ball throw showed moderate reliability (ICC = 0.70). Convergent validity analysis revealed strong correlations across all performance measures, ranging from 0.885 to 0.996. Discriminant validity analysis indicated low correlations between unrelated constructs, confirming that each test measured distinct physical performance components. The results support the SRTTB as a valid and reliable instrument for identifying athletic talent among individuals with intellectual disabilities. The findings provide practical implications for coaches, educators, and researchers in developing evidence-based training and talent identification programs. Abstract in Indonesia. Penelitian bertujuan untuk mengevaluasi validitas konstruk dan reliabilitas Track and Field SportRec Talent Test Battery (SRTTB) yang dirancang bagi individu dengan disabilitas intelektual. Identifikasi bakat olahraga memiliki peran penting dalam mengoptimalkan potensi atlet serta mendukung pengembangan olahraga yang inklusif. Sebanyak 74 siswa laki-laki dengan disabilitas intelektual berusia 14–20 tahun dari sebuah sekolah di Klang berpartisipasi dalam penelitian. Partisipan mengikuti serangkaian tes performa fisik yang meliputi standing long jump, lari sprint 30 m, push-up, seated medicine ball throw, standing overhead medicine ball throw, standing backward overhead medicine ball throw, dan tes kebugaran intermiten 20 m. Analisis data dilakukan menggunakan IBM SPSS versi 30 untuk menguji validitas konstruk dan reliabilitas tes–ulang. Validitas konstruk dianalisis melalui validitas konvergen dan diskriminan, sedangkan reliabilitas dievaluasi menggunakan Intraclass Correlation Coefficient (ICC). Hasil penelitian menunjukkan reliabilitas sangat baik pada tes standing long jump (ICC = 0,94), sprint 30 m (ICC = 0,89), push-up (ICC = 0,97), standing overhead medicine ball throw (ICC = 0,84), standing backward overhead medicine ball throw (ICC = 0,91), dan tes VO₂max (ICC = 0,99). Tes seated medicine ball throw menunjukkan reliabilitas sedang (ICC = 0,70). Analisis validitas konvergen menunjukkan korelasi yang kuat pada seluruh ukuran performa fisik dengan rentang nilai 0,885–0,996. Analisis validitas diskriminan menunjukkan korelasi rendah pada konstruk yang tidak berkaitan sehingga setiap tes terbukti mengukur komponen performa fisik yang berbeda. Hasil penelitian mendukung SRTTB sebagai instrumen yang valid dan reliabel untuk identifikasi bakat atletik pada individu dengan disabilitas intelektual. Temuan penelitian memberikan implikasi praktis bagi pelatih, pendidik, dan peneliti dalam mengembangkan program pelatihan dan identifikasi bakat berbasis bukti.